Analysis the Impact of CFO–CIO Collaboration and Digital Governance on the Financial Performance of Technology Companies in West Java - Ahalik Ahalik; Irwan Irawadi Barus; Fenty Astrina; Eko Sudarmanto; Fadilla Muhammad Mahdi (West Science Interdisciplinary Studies, 2026)
This study examines the impact of Chief Financial Officer (CFO)–Chief Information Officer (CIO) collaboration and digital governance on the financial performance of technology companies in West Java. In the context of rapid digital transformation, the alignment between financial and technological functions has become a critical factor in organizational success. This research adopts a quantitative approach using primary data collected from 120 respondents through structured questionnaires measured on a Likert scale. Data analysis was conducted using IBM SPSS Statistics version 25, including descriptive statistics, validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that CFO–CIO collaboration has a positive and significant effect on financial performance, demonstrating that effective coordination between financial and IT leadership enhances strategic decision-making and resource allocation. Digital governance also shows a positive and significant influence, highlighting the importance of structured policies, risk management, and accountability in managing digital initiatives. Simultaneously, both variables significantly affect financial performance, with a coefficient of determination (R²) of 0.61, indicating that 61% of the variation in financial performance can be explained by the model. These findings suggest that collaboration and governance mechanisms play a complementary role in driving organizational performance. This study contributes to the literature by providing empirical evidence on the strategic role of cross-functional collaboration and digital governance in emerging markets. Practically, the findings offer insights for organizations to strengthen CFO–CIO partnerships and implement effective governance frameworks to enhance financial outcomes in the digital era.